2008
DOI: 10.1007/s11130-008-0082-z
|View full text |Cite
|
Sign up to set email alerts
|

Jamaican Bitter Yam Sapogenin: Potential Mechanisms of Action in Diabetes

Abstract: Sapogenin has been proposed to be the active component responsible for the beneficial effects of Jamaican bitter yam (Dioscorea polygonoides) in the management of diabetes. Most of the research activities on bitter yam have focused on the role sapogenin play in the management of diabetes. Changes in weight, activities of carbohydrate digestive and transport enzymes, alterations in the intestinal morphology, changes in blood lipids, reduction in lipid peroxidation and the prevention of liver damage associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Of these, the saponin content is higher than those of the other two substances. It has been demonstrated that some saponin components have hypoglycemic effects 32, 33. Therefore, we investigated the effect of the saponin fraction from fenugreek on adipocyte differentiation in 3T3‐L1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, the saponin content is higher than those of the other two substances. It has been demonstrated that some saponin components have hypoglycemic effects 32, 33. Therefore, we investigated the effect of the saponin fraction from fenugreek on adipocyte differentiation in 3T3‐L1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…There are several reports suggesting that diosgenin-rich food sources such as fenugreek seeds and yam tubers contribute to anti-diabetic effects in experimental models (Basch et al, 2003;Omoruyi, 2008). Evidence from human clinical trials clearly suggests that fenugreek seeds improve blood glucose and other metabolic parameters leading to treatment of diabetes (Basch et al, 2003).)…”
Section: Diabetesmentioning
confidence: 99%
“…14 Saponins such as diosgenin-related compounds also reportedly slow the rate of gastric emptying, possibly through reduced activity of gastrointestinal enzymes. 15 We previously reported that a sapogenin-rich preparation from Jamaican bitter yam (D. polygonoides) significantly reduced blood cholesterol in hypercholesterolemic SpragueDawley rats. 16 However, the mechanism by which bitter yam lowers blood cholesterol is not known.…”
mentioning
confidence: 96%